The importance of microbiological quality control in phytotherapy products and medicinal plants (Research, Society and Development, 2022)
Phytotherapeutic drugs and medicinal plants have been used to treat diseases for thousands of years and the expansion of their use has increased the need for a more rigorous microbiological quality control, since microbial contamination can affect the quality of the product and the health of the individual. From this, the present study aimed to analyze different methodologies applied in the microbiological quality control of phytotherapics and medicinal plants, in order to highlight their importance. This is, therefore, a literature review, in which articles published between 2016 and 2022 were analyzed. More than half of the selected articles (55%) addressed Phytotherapeutic drugs or medicinal plants with high microbial contamination, which can cause changes chemical characteristics of plant metabolites, reducing their therapeutic efficacy and generating toxic substances, in addition to the risk of infections by potential pathogens, being extremely harmful to the patient. However, not all articles correctly followed the microbiological control recommended by the legislation, which shows the need to carry out rigorous microbiological quality control and the adequacy of procedures to current legislation, in order to guarantee greater quality, safety and effectiveness of the product that is delivered to the patient. In view of the above, it is considered that Phytotherapeutic drugs should be analyzed with the same rigor as synthetic medicines, in which microbiological control must occur at all stages of the production process, in order to minimize the risks of contamination in the product and, consequently, commercialize products suitable for human consumption.